Emergency Department Burden of Nausea and Vomiting Associated With Cannabis Use Disorder: US Trends From 2006 to 2013. Issue 9 (October 2018) - Bollom, Andrea; Austrie, Jasmine; Hirsch, William; Nee, Judy; Friedlander, Daniel; Iturrino, Johanna; Ballou, Sarah; Lembo, Anthony
Abstract : Background and Aims: Chronic cannabis use is associated with nausea and vomiting that may lead to emergency department (ED) visits, multiple diagnostic tests, and procedures. The aim of this study was to analyze recent trends in ED visits for vomiting associated with cannabis use disorder between 2006 and 2013. Methods: Data were obtained from the National Emergency Department Sample records in which vomiting (ICD-9-CM codes 787.01, 787.03, and 536.2) was a primary diagnosis in combination with cannabis abuse or dependence (304.3, 304.30, 304.31, 304.32, 304.33, 305.2, 305.20, 305.21, 305.22, and 305.23) and were seen in the ED between 2006 and 2013. The National Emergency Department Sample collects data from more than 25 million visits in over 950 EDs and is weighted to provide national estimates. Results: The rate of ED visits for vomiting with cannabis use disorder from 2006 compared with 2013 increased from 2.3 to 13.3 per 100, 000 ED visits, while the mean inflation-adjusted costs increased 68.5% from $2758.43 to $4647.62, respectively. Men between the ages of 20 and 29 were the most common group to present to the ED for vomiting with cannabis use disorder. The Midwest and West had the higher rates of ED visits for vomiting with cannabis use disorder compared with the Northeast and South. Conclusions: ED visits for vomiting associated with cannabis use disorder is common and is associated with significant medical costs. Further research on the role of cannabis use in nausea and vomiting is warranted.